Investigating the influence of digital transformation, budgeting and budgetary control on the financial performance of SMEs - Oziegbe Simeon Ebhota; Yao Hongxing; Agyemang Kwasi Sampene (Scientific African)
The study delves into the challenges and opportunities SMEs face in South-West Nigeria, focusing on the transformative impacts of digitalization, big data analytics, customer experience enhancement, and stringent budgeting controls on their financial performance. The research analyzes data from 825 SMEs through Partial Least Squares Structural Equation Modelling (PLS-SEM) analyze the data. The findings indicate that digital transformation significantly boosts customer experience, big data analytics, and budgetary controls. Enhanced customer experience and effective big data utilization reciprocally improve budgetary control processes, which are crucial for financial performance. The study reveals the mediating roles of customer experience and big data analytics in the relationship between digital transformation and budgeting control, highlighting the interconnectedness of these factors. Financial efficiency also emerges as a significant moderator in the nexus between budgetary control and financial performance, underscoring its influence on economic outcomes. This research proposed initiatives such as investments in customer relationship management systems, personalized services, and streamlined communication channels to create positive customer experiences that, in turn, positively influence budgeting outcomes.